How could runners rotate their bodies about the vertical axis so that the whole-body orientation could be maintained along a curved path? - Sato, T.; Yanai, T. (International Journal of Sport & Health Science, 2019)
The purpose of the present study was to determine how runners sprinting along a curved path could rotate their whole body about the vertical axis to maintain their stance so that they continually faced the ever-changing running direction. Ten healthy men were asked to run at 5 m/s along a straight path (RS) and a curved path with a 5-m radius (RC). The running direction during RC was counterclockwise as viewed from above (CCW). A motion capture system (240 Hz) was used to record the three-dimensional coordinates of the reflective markers attached to each subject. The changing patterns of the angular momentum of each segment and the average angular momentum of the whole body in each contact and flight phase were compared between the two movements. In all the phases, the average angular momentum during RC was significantly directed more toward the CCW direction than that during RS. In contrast, the angular momentum of the head and trunk during RS changed periodically from positive to negative values, while that during RC continued to exhibit positive values throughout the stride cycle. The changing pattern of the angular momentum of the left leg during RC was in the phase opposite to that during RS because the subjects swung the left leg on their right side. The left leg moved in an elliptical trajectory in a direction opposite to the rotation of the whole body on the horizontal plane during RC; this presumably generated reactional rotation effects on the other segments to maintain stance that allowed the subject to keep facing the running direction.